Remote training in cybersecurity for industrial control systems. Issue 17 (2022) - Domínguez, Manuel; Pérez, Daniel; Morán, Antonio; Alonso, Serafín; Prada, Miguel A.; Fuertes, Juan J.
Abstract: Cybersecurity is a key subject for digital transformation where institutional, industrial and educational sectors should be involved in a coordinated way. Currently, there is a lack of workforce with essential competences to apply secure solutions in an industrial environment. For that reason, in order to address this increasing demand, universities promote industrial cybersecurity courses and related programs. But training of future cybersecurity professionals in the industrial sector requires appropriate frameworks that facilitate teaching students a range of evolving technologies. In this work, a platform for remote training in cybersecurity is proposed using cabinets that include specific elements for automation and control as well as additional resources for administration and communication tasks. The platform allowed the development of two cybersecurity courses whose students were asked for feedback about the structure of the laboratory, its operation and also the learning process. The results show a wide acceptance of the platform used in the course and an improvement of students' motivation in the subject.